2016
DOI: 10.1038/aps.2015.124
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide B protects human umbilical vein endothelial cells against xenobiotic injuries via PXR activation

Abstract: Ginkgolide B exerts anti-apoptotic and anti-inflammatory effects on endothelial cells via PXR activation, suggesting that a PXR-mediated endothelial detoxification program may be important for protecting endothelial cells from xeno- and endobiotic-induced injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
(41 reference statements)
2
9
0
Order By: Relevance
“…FXR have been identified as critical nuclear receptors which bind to the promoters of target genes to regulate transcriptional activity of downstream target genes after ligand-activated nuclear translocation (Meyer Zu Schwabedissen et al, 2010;Xu et al, 2016;Zhou et al, 2016). In this study we found that berberine promoted nuclear translocation and activation of FXR and LXRa, similar to other Chinese herbal medicines such as ginkgolide b (Zhou et al, 2016) and dihydroartemisinin (Xu et al, 2016).…”
Section: A B Csupporting
confidence: 58%
See 1 more Smart Citation
“…FXR have been identified as critical nuclear receptors which bind to the promoters of target genes to regulate transcriptional activity of downstream target genes after ligand-activated nuclear translocation (Meyer Zu Schwabedissen et al, 2010;Xu et al, 2016;Zhou et al, 2016). In this study we found that berberine promoted nuclear translocation and activation of FXR and LXRa, similar to other Chinese herbal medicines such as ginkgolide b (Zhou et al, 2016) and dihydroartemisinin (Xu et al, 2016).…”
Section: A B Csupporting
confidence: 58%
“…FXR have been identified as critical nuclear receptors which bind to the promoters of target genes to regulate transcriptional activity of downstream target genes after ligand-activated nuclear translocation (Meyer Zu Schwabedissen et al, 2010;Xu et al, 2016;Zhou et al, 2016). In this study we found that berberine promoted nuclear translocation and activation of FXR and LXRa, similar to other Chinese herbal medicines such as ginkgolide b (Zhou et al, 2016) and dihydroartemisinin (Xu et al, 2016). In addition, berberine significantly increased the expression of FXR protein and mRNA at 10 and 25 mM, but only moderately upregulated the expression of FXR protein at 50 mM, while the mRNA expression was still significantly upregulated, suggesting that FXR may be subjected to a series of posttranscriptional regulations, such as phosphorylation, acetylation, and glycosylation (Chang, 2009;Sugatani et al, 2014).…”
Section: A B Cmentioning
confidence: 99%
“…Cell viability was evaluated using a cell counting kit-8 (CCK-8) assay kit (Dojindo Corp., Tokyo, Japan) as described Previously ( Zhou et al , 2016 ). Briefly, in 96-well plates 10 μL CCK-8 solution was added to 90 μL RPMI-1640 in each well, then cells were incubated at 37°C for 0.5-4 h, after which absorbance at an asorbrance of 450 nm, was measured using a 2030 Multilabel VICTOR TM X5 Reader.…”
Section: Methodsmentioning
confidence: 99%
“…8 Previous studies have reported that GB has beneficial biological effects on the protection of endothelial cells. 9 In vitro and in vivo experiments have also shown that GB exerts an anti-inflammatory effect on different cells. 10−12 However, the effects and underlying mechanism of GB in OA have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%